Pemikiran Husein Muhammad Tentang Khitan Wanita - Fauziah, Nelli (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2015)
Gender issue is seemingly an interesting topic to discuss. One of the important figure on gender is a Husein Muhammad on his view about female circumcision. This study highlights about the analysis of Islamic law against Husein Muhammad's thought on female circumcision in relation to the fulfillment of the couple's biological needs. The result of the study concludes that: First, Husein Muhammad argues that female circumcision is equal to FGM, which circumcision is conducted by taking the clitoris, so it causes women to be frigid. According to him, the phenomenon of the female circumcision has no textual argumentation from both of al-Qur'an and al-Hadith. It, he said, is not the practice of Islam but rather adopted from the Jahiliyyah tradition and has no benefit (maslahah). Secondly, in his legal reasoning process, he uses qiyas (analogy) and maslahah mursalah (the restricted benefit). Third, Muhammad Husein's thought about female circumcision in terms of Islamic law is not correct. Due to the Islamic law, according to the instruction of Prophet Muhammad, female circumcision is done by taking a skin membrane that covers the clitoris, not taking the clitoris. So that women will not lose her biological sexual pleasure during sexual intercourse. By fulfilling the biological needs between husband and wife then it can create a harmonious household, sakinah, mawaddah and rahmah. [Persoalan gender seakan tidak pernah selesai untuk dibahas. Salah satu tokoh gender yang populer adalah Husein Muhammad yang pernah membahas tentang khitan wanita. Penelitian ini akan membahas bagaimana analisis hukum Islam terhadap pemikiran Husein Muhammad tentang khitan wanita dalam kaitannya dengan pemenuhan kebuthan biologis suami istri. Hasil penelitian menyimpulkan: Pertama, Husein Muhammad berpendapat bahwa khitan wanita adalah sama dengan FGM, yakni khitan dilakukan dengan cara mengambil klitoris, sehingga menyebabkan wanita frigid. Husein menilai dasar hukum khitan wanita tidak ada dalam nash baik dari al-Qur'an maupun hadis. Praktik khitan wanita bukan syari'at Islam, melainkan mengadopsi tradisi jahiliyah yang tidak ada unsur maslahah-nya, sehingga hukumnya haram. Kedua, dalam melakukan istinbat hukum, Husein Muhammad menggunakan metode qiyas dan maslahah al-mursalah. Ketiga, Pemikiran Husein Muhammad tentang khitan wanita ditinjau dari hukum Islam adalah tidak tepat. Karena dalam syari'at Islam, sesuai petunjuk Rasulullah, khitan wanita dilakukan dengan cara mengambil selaput kulit yang menutupi klitoris, bukan mengambil klitoris. Sehingga wanita tidak akan kehilangan kenikmatan seksual ketika berhubungan biologis. Dengan terpenuhinya kebutuhan biologis antara suami istri ini maka terciptalah sebuah rumah tangga yang harmonis, sakinah, mawaddah dan rahmah.]